2020
DOI: 10.21203/rs.3.rs-25644/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring Dependence of COVID-19 on Environmental Factors and Spread Prediction in India

Abstract: The pandemic of “Corona Virus Disease 2019” or COVID-19 has taken the world by storm. Majority of nations of the world have been challenged by the novel coronavirus, which is supposedly of zoonotic origin and is known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The present work attempts to evaluate the spread of COVID-19 in India. The methodology of assessment uses SEIR (Susceptible-Exposed-Infectious-Removed) model to establish the impact of socio-behavioural aspect, especially social dis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…It is evident that various preventive measures with social distancing norms have been taken to regulate the transmission of COVID-19 pandemic, whereas these preventive measures directly affect the growth of global economy, human health and environment (Sarkodie and Owusu 2020). Similarly, another study established that social distancing rule is the most effective way for administration to regulate the contagious nature of COVID-19 pandemic in India (Bherwani et al 2020). It is undoubtedly observed that the per day emission rate from road traffic sector was the lowermost on the day of national Janta Curfew in India (CPCB 2009(CPCB , 2020.…”
Section: Air Quality Scenarios Of Europe and Asian Countries During Cmentioning
confidence: 99%
“…It is evident that various preventive measures with social distancing norms have been taken to regulate the transmission of COVID-19 pandemic, whereas these preventive measures directly affect the growth of global economy, human health and environment (Sarkodie and Owusu 2020). Similarly, another study established that social distancing rule is the most effective way for administration to regulate the contagious nature of COVID-19 pandemic in India (Bherwani et al 2020). It is undoubtedly observed that the per day emission rate from road traffic sector was the lowermost on the day of national Janta Curfew in India (CPCB 2009(CPCB , 2020.…”
Section: Air Quality Scenarios Of Europe and Asian Countries During Cmentioning
confidence: 99%
“…The recent outbreak of coronavirus disease, termed as COVID-19, has raised global concerns and led to total lockdown in many countries (WHO 2020a ; Gautam and Trivedi 2020 ; Bherwani et al 2020b ; Wang et al 2020a ). The disease is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) (Gautam and Hens 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…Bherwani et al 2020 [89] The impact of COVID-19 incidence was analysed using SEIR model, and the impact of temperature and humidity was statistically analysed using Response Surface Methodology in India The impact of government-imposed lockdown was considered in the SEIR (compartmental) model. Further, ANOVA and higher-order polynomial functions of RSM techniques provide much better estimates.…”
Section: Discussionmentioning
confidence: 99%